Redistribution and the Monetary-Fiscal Policy Mix - Saroj Bhattarai; Jae Won Lee; Choongryul Yang (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We show that the effectiveness of redistribution policy in stimulating the economy and improving welfare is directly tied to how much inflation it generates, which in turn hinges on monetary-fiscal adjustments that ultimately finance the transfers. We compare two distinct types of monetary-fiscal adjustments: In the monetary regime, the government eventually raises taxes to finance transfers while in the fiscal regime, inflation rises, effectively imposing inflation taxes on public debt holders. We show analytically in a simple model how the fiscal regime generates larger and more persistent inflation than the monetary regime. In a quantitative application, we use a two-sector, two-agent New Keynesian model, situate the model economy in a Covid-19 recession, and quantify the effects of the transfer components of the Coronavirus Aid, Relief, and Economic Security (CARES) Act. We find that the transfer multipliers are significantly larger under the fiscal regime—which results in a milder contraction—than under the monetary regime, primarily because inflationary pressures of this regime counteract the deflationary forces during the recession. Moreover, redistribution produces a Pareto improvement under the fiscal regime.
Keywords: E53; E62; E63; 330; household heterogeneity; redistribution; monetary-fiscal policy mix; transfer multiplier; welfare evaluation; Covid-19; CARES Act